Effects of Chronic Maltreatment and Maltreatment Timing on Children's Behavior and Cognitive Abilities - Jaffee, Sara R. (2010)
BACKGROUND: Chronic maltreatment has been associated with the poorest developmental outcomes, but its effects may depend on the age when the maltreatment began, or be confounded by co-occurring psychosocial risk factors. METHOD: We used data from the National Survey of Child and Adolescent Well-Being (NSCAW) to identify four groups of children who varied in the timing, extent, and continuity of their maltreatment from birth to 9 years. Internalizing and externalizing problems, prosocial behavior, and IQ were assessed 21 months, on average, following the most recent maltreatment report. RESULTS: Children maltreated in multiple developmental periods had more externalizing and internalizing problems and lower IQ scores than children maltreated in only one developmental period. Chronically maltreated children had significantly more family risk factors than children maltreated in one developmental period and these accounted for maltreatment chronicity effects on externalizing and internalizing problems, but not IQ. The timing of maltreatment did not have a unique effect on cognitive or behavioral outcomes, although it did moderate the effect of maltreatment chronicity on prosocial behavior. CONCLUSION: There is a need for early intervention to prevent maltreatment from emerging and to provide more mental health and substance use services to caregivers involved with child welfare services.